2019
DOI: 10.1016/j.joca.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis year in review 2018: biomarkers (biochemical markers)

Abstract: The aim of this narrative review is to summarize important findings from biochemical marker studies relevant to osteoarthritis (OA) in the context of new discoveries and clinical and scientific need. Design: We conducted a systematic search of electronic medical databases (Embase, Medline, Web of Science, Cochrane central) between 01-03-2017 and 31-03-2018. The search was restricted to human studies, English language and full text available publications while reviews were excluded. Only papers describing prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 91 publications
2
42
0
1
Order By: Relevance
“…Although loss of articular cartilage is the hallmark pathological feature in OA, disease progression involves early subchondral trabecular bone remodeling resulting in decreased trabecular bone mass and formation of osteophytes at the joint margins [McCann et al, 2017]. Changes in bone remodeling are frequently present early in the OA process [Saberi Hosnijeh et al, 2018]. Therefore, we investigated the subchondral trabecular bone microarchitecture by micro‐CT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although loss of articular cartilage is the hallmark pathological feature in OA, disease progression involves early subchondral trabecular bone remodeling resulting in decreased trabecular bone mass and formation of osteophytes at the joint margins [McCann et al, 2017]. Changes in bone remodeling are frequently present early in the OA process [Saberi Hosnijeh et al, 2018]. Therefore, we investigated the subchondral trabecular bone microarchitecture by micro‐CT.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies showed an elevated level of IL‐1β in synovial fluid, synovial membrane, cartilage, and subchondral trabecular bone layer in patients with OA [Jotanovic et al, 2012; Sohn et al, 2012; Wojdasiewicz et al, 2014]. Animal studies suggested that inhibiting IL‐1β may reduce pain and slow structural progression in OA [Saberi Hosnijeh et al, 2018]. IL‐1β can increase synthesis and release of many proteolytic enzymes that decompose articular cartilage, which include MMPs, mainly stromelysin‐1 (MMP‐3) and collagenase 3 (MMP13).…”
Section: Discussionmentioning
confidence: 99%
“…For example, inflammatory cytokines (eg, tumor necrosis factor α) and degradative enzymes (eg, matrix metalloproteinases) are helpful to cartilage degradation . These results suggested that OA had influence on different structures of human joints through multiple causal pathways . Recently, some advances have been made in distinguishing subgroups of patients with distinct pathology .…”
Section: Discussionmentioning
confidence: 99%
“…The process is also accompanied by the expression of osteoclastic genes, including nuclear factor of activated T cells 1 (NF‐ATc1), c‐Fos, c‐Fms, receptor activator of NF‐κB (RANK), dendrocyte expressed seven transmembrane protein (DC‐STAMP), and cathepsin K. Notably, accumulating studies indicate that OCs are involved in the initiation and progression of inflammatory bone diseases, including osteoarthritis . The increase of proinflammatory cytokines, such as interleukin‐1 β (IL‐1β), tumor necrosis factor‐α (TNF‐α), and interleukin‐17A (IL‐17A), in osteoarthritis synovial fluid (OASF) or subchondral bones lead to overactive OC formation and joint damage . Moreover, cell surface molecules in bone stromal cells typically act as pro‐osteoclastic factors .…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] The increase of proinflammatory cytokines, such as interleukin-1 β (IL-1β), tumor necrosis factor-α (TNF-α), and interleukin-17A (IL-17A), in osteoarthritis synovial fluid (OASF) or subchondral bones lead to overactive OC formation and joint damage. [12][13][14] Moreover, cell surface molecules in bone stromal cells typically act as pro-osteoclastic factors. [15][16][17][18] Furthermore, inflammatory osteoclastogenesis was reported to contribute to bone infection-induced osteoporosis.…”
Section: Introductionmentioning
confidence: 99%